Internet Addiction and Related Psychological Factors Among Children and Adolescents in China During the Coronavirus Disease 2019 (COVID-19) Epidemic - Dong, Huixi; Yang, Fangru; Lu, Xiaozi; Hao, Wei (Frontiers in Psychiatry, 2020)
Background: The Coronavirus disease 2019 (COVID-19) is an infectious disease presenting a major threat to public health. This study aims to assess Internet use characteristics and objectively examine the potential psychological factors associated with Internet addiction (IA) during the COVID-19 epidemic. Methods: A cross-sectional, anonymized, self-reported survey was conducted among Chinese children and adolescents aged 6 to 18 years old. Participants completed questionnaires containing Young’s Internet Addiction Test (IAT) and the Depression, Anxiety and Stress Scale (DASS-21), and questions regarding demographic information and Internet use characteristics. Results: A total of 2050 participants (mean age:12.34±4.67 years old, female: 48.44%) were enrolled. Fifty-five (2.68%) participants met the criterion for addictive Internet use (IAT≥70), while six hundred and eighty-four (33.37%) participants were classified as problematic Internet users (69≥IAT≥40). Internet usage had grown during the COVID-19 epidemic, including the frequency and duration of recreational Internet use, and the frequency of stay-up Internet use. A linear regression analysis showed female gender (β=-0.091, p<0.001), age (β=0.066, p=0.001), depression (β=0.257, p<0.001) and stress (β=0.323, p<0.001) were significantly correlated with the IAT total scores (R=0.539, R2=0.291, p<0.001). Conclusions: We observed excessive Internet use among Chinese children and adolescents during the outbreak of COVID-19. Age, gender, depression and stress were the potential key factors affecting IA. Extended family and professional support should be considered for vulnerable individuals during these unprecedented times.